MEASURING AND ANALYZING THE IMPACT OF SOME MONETARY INDICATORS ON ACHIEVING ECONOMIC STABILITY IN IRAQ FOR THE PERIOD (2010-2024) (World Economics and Finance Bulletin, 2025)
The research aims to measure and analyze the impact of some monetary indicators in achieving economic stability and the monetary indicators that have been focused on are the nominal interest rate, the real interest rate, the parallel exchange rate and the consumer price index. Either achieving economic stability, focusing on both the gross domestic product and the percentage of economic activities contributing to the Iraqi economy at constant prices. Spatial boundaries were represented in the data published by the Central Bank - Directorate General of Statistics and Research. The time limits of the search were a continuous time series of fifteen years from (2010- 2024) due to the availability of information and data on the variables of searching for the studied variables. The research reached several conclusions, the most important of which was that the reality of the Iraqi economy cannot control the growth of the money supply through its various tools, but pointed to the opposite, as growth rates were taken in some monetary indicators with increasing growth rates of public spending, which confirms the strength of the impact of the government demand function on money affected by government income from oil resources.
Keywords: Monetary indicators; achieving economic stability